Animal Welfare in Colombian Sheep-Goat Production Systems - Acero , Víctor Manuel (Spei Domus, 2014)
In Colombia, livestock systems or production systems are focused on species with the greatest export potential or highest national consumption. These are poultry (meat, eggs, genetics), cattle (milk, meat, genetics), pigs (meat, genetics) and fish. There is also smaller scale production of buffalos, sheep/goats, rabbits and guinea pigs. National standards related to primary production have centered on good practices for cattle, poultry and pigs, and there are currently norms for the slaughter of these animals. The industry for these species is generally well developed, albeit with some gaps in the areas of animal welfare, traceability, and disease control and surveillance systems, food-safety systems and compliance with international standards for exportation. Data from 2012 shows that Colombian livestock production primarily consists of 27 million head of cattle, 25 million birds (chickens/hens), 2.5 million horses, 1.6 million pigs, 1.3 million goats, and 1.1 million sheep, among other animals. This shows an imbalance in the agricultural sector, where there is a clear tendency towards traditional production species. Today, there are approximately 2.5 million head of sheep and goats when the two species are taken together.